Seasonal variation of yield and composition in extracts from immature and mature Eucalyptus bosistoana leaves - Rajapaksha, Chamira; Apiolaza, Luis Alejandro; Squire, Marie A.; Altaner, Clemens (Flavour and fragrance journal, 2023)
Seasonal variations of yield and composition in microwave extracts from mature and immature Eucalyptus bosistoana leaves were monitored for 2 years. The highest yield (average 16.7 μL/g (fresh)) and percentage of 1,8‐cineole (average 67.1%) were obtained from the leaves collected during summer and the lowest during winter. Mature leaves contained a significantly higher (p ≤ .001) proportion of 1,8‐cineole in their extract (60.9%) than immature leaves (44.6%). Total yield ranged from 3.0 to 27.0 μL/g (fresh) in mature leaves and from 6.0 to 26.7 μL/g (fresh) in immature leaves. Significant differences between half‐sibling families were observed, indicating genetic control of these traits. E. bosistoana leaf extracts could be comparable in quality and quantity to that of E. globulus, the species dominating global essential eucalyptus oil production. Oil quality and quantity could be optimized by harvesting mature leaves during summer from superior families. Mature leaves possessed higher 1,8‐cineole proportions but contained less total oil than immature leaves. E. bosistoana essential oil of higher quality and quantity can be obtained by harvesting in summer.